PENGARUH PEMBELAJARAN SAS DENGAN MEDIA PAFLACA TERHADAP KEMAMPUAN MEMBACA PERMULAAN - Chasanah, Siti Nur; Rasidi, Rasidi; Triana, Putri Meinita (Prosiding University Research Colloquium, 2021)
This research aims to know the influence of learning SAS with the media Paflaca to the ability to read the beginning of the 1st grade students of primary School in the Village of Tegalarum. This research is an experimental research on the design of the Pre- Experimental Design type of One-Group Pretest-posttest. This research was conducted in the Village of Tegalarum Kecamatan Borobudur, Magelang Regency. Before carrying out research in the village the researchers conducted observations of the pre-study on student Elementary school class I found the problem is reading the beginning of the still low. The subject of this research is the students of class I in the Village of Tegalarum which amounted to 16 students, which consisted of 10 female students and 6 male students. Data collection using the method of the test. This test is used before and after a given treatment and the analysis used in this research is the Wilcoxon Signed Rank Test with programSPSS version of 25.00. This research was conducted in the month of July 2021. The results showed that the method of learning SAS-assisted media Paflaca affect the ability to read the beginning. Evidence of improved student learning outcomes, namely the presence of a significant difference between the value of pretest and the value of the posttest, namely the average value of pretest 58,1 while the average value of posttest were 79.1 and the results of the Wilcoxon Signed Rank Test obtained value (2- tailed)-3,551 with a significance value of 0.000.